1994
DOI: 10.1007/bf02541428
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic production and physicochemical characterization of uncommon wax esters and monoglycerides

Abstract: Wax esters from fatty alcohols and uncommon fatty acids were synthesized in yields up to 90% when commercially available microbial lipases from Rhizomucor miehei (Lipozym ewM) and Candida antarctica (SP 435) were used with limited water content in nonpolar solvents under mild conditions. The corresponding fatty acids were prepared by chemical conversion of naturally occurring resources (agricultural surpluses). Also, when phenylboronic acid was added as solub'dizing agent in a nonpolar solvent, the direct enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Methyl ricinoleate and ricinoleyl alcohol were used to lead to hydroxy C~O unsaturated wax-esters. Some ricinoleic acid esters prepared by enzymatic catalysis, have already been described [31] as well as other uncommon wax-esters [32]. The results of the lipozyme catalyzed synthesis of new hydroxy wax-esters, are reported in Scheme 1.…”
Section: Resultsmentioning
confidence: 98%
“…Methyl ricinoleate and ricinoleyl alcohol were used to lead to hydroxy C~O unsaturated wax-esters. Some ricinoleic acid esters prepared by enzymatic catalysis, have already been described [31] as well as other uncommon wax-esters [32]. The results of the lipozyme catalyzed synthesis of new hydroxy wax-esters, are reported in Scheme 1.…”
Section: Resultsmentioning
confidence: 98%
“…fine-chem Ltd. (Mumbai, India). Lauryl myristyl alcohol {C 12 : 70-75%, C 14 : 25-30%, C 16 : <5%}, cetyl alcohol (purity 98%), stearyl alcohol (purity 98%), ceto stearyl (PS) {C 12 : <2%, C 14 <7%, C 16 : 55-65%, C 18 : 35-45%, C 20 : <2%}, ceto stearyl (TA) {C 12 : <2%, C 14 : <7%, C 16 : 25-35%, C 18 : 60-67%, C 20 : <2%}, ceto stearyl (50%:50%), behenyl alcohol (purity 93%) were procured from Godrej Soaps Ltd. (Mumbai, India). Myristyl alcohol (purity 98%) was procured from Unilab Chemicals and Pharmaceuticals, (Mumbai, India).…”
Section: Methodsmentioning
confidence: 99%
“…In the recent past, wax esters have been synthesized by enzyme-catalyzed reactions [12][13][14][15][16][17]. Primary aliphatic alcohols, R-CH 2 OH, react with H 2 O 2 under mild conditions in a two-phase liquid-liquid system with ethylene dichloride as a solvent in the presence of Br 2 or HBr to yield selectively the corresponding ester [18].…”
Section: Introductionmentioning
confidence: 99%
“…nonionic oligomers which have potential application in the field of surfactants and cosmetics. [30][31][32] Therefore, oligomerization of glycidol (Table 3) was analyzed with respect to the reaction conditions. Various kinds of commercially available lipases were screened with respect to the polymerization of glycidol using 10% enzyme (wt.-% to glycidol) at 40 8C for 1 d. It was found that glycidol was polymerized in bulk by the enzyme producing the watersoluble poly(glycidol).…”
Section: Polymerization Of Oxiranes Gpe and Glycidolmentioning
confidence: 99%